Integrated Analysis of Coding and Non-coding RNAs Reveals the Molecular Mechanism Underlying Salt Stress Response in Medicago truncatula - An, Yixin; Su, Haotian; Niu, Qichen; Yin, Shuxia (Frontiers in Plant Science, 2022)
Salt stress is among the most severe abiotic stresses in plants worldwide. Medicago truncatula is a model plant for legumes and analysis of its response to salt stress is helpful for providing valuable insights into breeding. However, few studies have focused on illustrating the whole-transcriptome molecular mechanism underlying salt stress response in Medicago truncatula. Herein, we sampled the leaves of Medicago truncatula treated with water or NaCl and analyzed the characteristics of its coding and non-coding RNAs. We identified a total of 4,693 differentially expressed mRNAs (DEmRNAs), 505 DElncRNAs, 21 DEcircRNAs, and 55 DEmiRNAs. Gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses revealed that their functions were mostly associated with metabolic processes. We classified the lncRNAs and circRNAs into different types and analyzed their genomic distributions. Furthermore, we predicted the interactions between different RNAs based on the competing endogenous RNA (ceRNA) theory and identified multiple correlation networks, including 27 DEmiRNAs, 43 DEmRNAs, 19 lncRNAs, and 5 DEcircRNAs. In addition, we comprehensively analyzed the candidate DEmRNAs and ceRNAs and found that they were involved in Ca+ signaling, starch and sucrose biosynthesis, phenylpropanoid and lignin metabolism, auxin and jasmonate biosynthesis, and transduction pathways. Our integrated analyses in salt stress response in Medicago truncatula revealed multiple differentially expressed coding and non-coding RNAs, including mRNAs, lncRNAs, circRNAs, and miRNAs, and identified multiple DEmRNA and ceRNA interaction pairs that function in many pathways, providing insights into salt stress response in leguminous plants.